The effect of coffee grounds compost and planting media on the growth and yield of kailan plants (Brassica oleracea L.) - Hutomo, Antoseno Priyo; Ritawati, Sri; Roidelindho, Kiki; Utama, Putra (Gema Wiralodra, 2024)
The research aimed to determine the effect of composting from coffee waste and planting media composition on the growth and yield of the kailan plant (Brassica oleracea L.). This research was conducted from June until September 2023 in Pagenjahan Village, Kronjo District, Tangerang Banten. The method used a Randomized Completely Block Design (RCBD) as factorial with two factors and analyzed using SPSS. The first factor was the Compost from Coffee Waste (K) which consisted of four levels namely; 0 g Coffee Waste (K1), 10 g Coffee Waste (K2), 20 g Coffee Waste (K3), and 30 g Coffee Waste (K3). The second factor was the Planting Media Composition (M) which consisted of three levels namely; Topsoil Planting Media (M1), Topsoil Planting Media + Rice Husk Charcoal 1:1 (M2), Topsoil Planting Media + Cocopeat 1:1 (M3). The results showed that compost from coffee waste with 20 g dose (K2) had the best effect on the number of leaves at 14 DAP (Days After Planting), leaf area, total fresh weight, fresh weight consumption, and dry weight parameters. Planting media composition with Topsoil Planting Media + Cocopeat 1:1 (M3) had the best effect on the leaf area parameter. There was an interaction between compost from coffee waste and planting media composition on plant height at 14 DAP and 28 DAP. Nasution (2014), coffee waste influences the growth and yield of long bean plants (Vigna sinensis L.) and the best concentration is 20 grams.